Synthesis and characterization of Lanthanide Mixed Complexes Using Ortho-vanillinmonoxime and Phenylureas as Ligands - Ghoshal, M.N.; Chawan, M.C. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of rare earth ions La3+, pr3+, Nd3+,Sm3+, Gd3+ and Dy3+ with ortho-vanillinmonoxime as primaryligand and N-phenylurea and N,N'-diphenylurea as secondaryligands have been prepared and characterised on the basis of theirelemental analysis, electronic and infrared spectra, thermal analysisand conductivity measurements.